A simulation study of gold nanoparticles localisation effects on radiation enhancement at the mitochondrion scale. (November 2019) - Francis, Z.; Montarou, G.; Incerti, S.; Bernal, M.; Zein, S.A.
Highlights: Clustered distributions of gold nanoparticles in a cell induce higher radiation effect than uniform distributions. The distance between nanoparticles clusters and cellular substructures affects the enhancement ratio. The radiation enhancement ratio depends on distant interactions like chemical species diffusion. Abstract: This paper presents a Monte-Carlo study focusing on the effects of gold nanoparticles on the energy deposition patterns produced by incident photons in the close vicinity of the mitochondrial network modeled as a tube. Spherical shaped gold nanoparticles of 30 nm diameter were placed in a micrometric (10 × 10 × 10  μ m 3 ) water phantom containing a tube of 300 nm diameter and 5  μ m length. The tube represented a mitochondrial fragment and nanoparticles were distributed in the water phantom outside the tube. Photons of 120 keV were simulated using the Geant4 Livermore processes and the Geant4-DNA electron processes to account for secondary electrons collisions. The Livermore processes took into account the Auger cascade inside the gold material. A data mining algorithm was then used to analyze the energy deposition clusters inside the water phantom and the tube. A comparison was made between the results obtained for a uniform distribution of nanoparticles and a vesicle distribution model. The results including energy deposition clusters are also compared to dose enhancement ratios.